IMPLEMENTATION OF MULTICULTURAL EDUCATION VALUES IN MERDEKA CURRICULUM AT SMAN 7 BEKASI CITY - Hermawan, Ibnu; Wilodati; Nurbayani, Siti (Universitas Muhammadiyah Surakarta, 2024)
Indonesia is a large country and has diversity in terms of ethnicity, religion, race, ethnicity, culture, language and so on. The pluralism of Indonesian society is a big challenge in maintaining unity and integrity. The world of education is one of the institutions that plays an important role in maintaining the integrity and unity of society through implementing the values of multicultural education in schools. multicultural education as a perspective that recognizes the political, social, and economic realities experienced by each individual in complex and culturally diverse human encounters and reflects the importance of culture, race, sexuality and gender, ethnicity, religion, social status, economics, and exceptions in the educational process. This research aims to get an in-depth picture of how multicultural education values are implemented in the independent curriculum at SMA Negeri 7 Bekasi City. The approach used in this research is a qualitative research approach with the method used is a case study. In the qualitative approach, researchers used interview data collection techniques, observation and documentation studies at SMAN 7 Bekasi City schools, selecting informants using purposive sampling techniques. The results of the research is the school community's understanding of the concept of multicultural education is very good because the school community already understands the essence of the concept of multicultural education, namely education about the values of diversity that exist in society, including diversity of ethnicity, religion, language, race, culture, gender and including differences in socio-economic background.